Manejo da adubação fosfatada da aveia preta e do consórcio milho/capim Marandu com inoculação por Azospirillum brasilense em sistema plantio direto - Dickmann, Lourdes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The growth of cultivated areas under no-tillage system in Brazil, is increasingly diversifying the ways in which production systems are deployed and managed. The high expenditure on agricultural inputs cause the production has high costs. Thus, the growing interest in the use of inoculants that in its composition have bacteria that promote plant growth, especially the search for sustainable agriculture with less environmental pollution combined with lower production costs. There fore, this study aimed to verify in a Oxisoil under irrigated conditions in the Cerrado: 1) the effect of phosphorus fertilization and inoculation with and without Azospirillum brasilense in oat seeds on their nutrition and dry matter shoots and roots yield; 2) to evaluate the residual effect of phosphate and decomposition of oat straw on growth and yield of corn with and without inoculation with A. brasilense and Marandu grass in the consortium; 3) after the period simulating the fence pasture (60 days after the corn harvest), assess the chemical and nutritional quality of Marandu grass, and the effect of their trash on the production components and winter bean productivity in succession ; and 4) the end of each crop cycle to evaluate the effect of treatments on soil fertility. The experimental design was a randomized block design with four replications in a factorial scheme 5 x 2, with five doses of P 2 O 5 (0, 30, 60, 120 and 240 kg ha - 1 ) broadcast applied at sowing oats IAPAR 61 cultivar, with and without seed inoculation with bacteria diazotrophic A. brasilense at a dose of 100 mL 25 kg -1 of seed. Each experimental unit (plot) consisted of 4.4 m wide and 10 m long, totaling 44 m 2 . Seeds inoculation oat by A. brasilense increased plant height, more dry matter of shoots and roots production. Also provided an increase of N and P in shoots, and N and Mg in root tissue culture. The phosphorus fertilization in oat increased the dry matter of shoots and roots ...

O crescimento das áreas cultivadas sob Sistema Plantio Direto (SPD) no Brasil, está cada vez mais diversificando as formas como os sistemas de produção são implantados e manejados. Os elevados gastos com insumos agrícolas fazem com que a produção tenha altos custos. Assim, cresce o interesse pelo uso de inoculantes que em sua composição possuam bactérias promotoras de crescimento de plantas, principalmente pela busca de uma agricultura sustentável com menor poluição ambiental aliado a redução dos custos de produção. Diante disso, o presente estudo objetivou verificar em um Latossolo Vermelho Distrófico, sob condições irrigadas no Cerrado: 1) o efeito da adubação fosfatada e da inoculação ou não com Azospirillum brasilense nas sementes de aveia preta sobre sua nutrição e produtividade de matéria seca da parte aérea e raízes; 2) avaliar o efeito residual da adubação fosfatada e da decomposição da palhada da aveia sobre o crescimento e produtividade do milho com e sem inoculação com Azospirillum brasilense e do capim-Marandu em consórcio; 3) após o período simulando a vedação do pasto (60 dias após a colheita do milho), avaliar a qualidade bromatológica e nutricional do capim-Marandu, e o efeito de sua palhada sobre os componentes da produção e produtividade do feijão de inverno em sucessão; e 4) ao final de cada ciclo produtivo avaliar o efeito dos tratamentos sobre a fertilidade do solo. O delineamento experimental utilizado foi o de blocos casualizados, com 4 repetições, em esquema fatorial 5 x 2, ou seja, cinco doses de P 2 O 5 (0; 30; 60; 120 e 240 kg ha -1 ) aplicadas a lanço na semeadura da aveia preta cultivar IAPAR 61, com e sem a inoculação das sementes com a bactéria diazotrófica Azospirillum brasilense, na dose de 100 mL 25 kg -1 de sementes. Cada unidade experimental (parcela) constituiu-se de 4,4 m de largura e 10 m de comprimento, perfazendo 44 m 2 . A inoculação das sementes de...
Keywords: Milho; Aveia; Inoculação; Fertilizantes fosfatados; Agrosilvicultura; Inoculation